The Development of Lake Toba Tourism Area Based on Tourism Village, in Meat Tourism Village, Toba Regency - Eko Soaloon Sianipar; Badaruddin Badaruddin; R. Hamdani Harahap (Budapest International Research and Critics University, 2021)
The tourism sector as one of the pillars of national development has an impact on foreign exchange earnings, regional income and also the absorption of investment and labor in various regions in Indonesia. The development of the Lake Toba Tourism Area is one of the government's priority areas in developing tourism. With the issuance of Presidential Regulation Number 46 of 2016 concerning the Lake Toba Authority Management Agency, it is an initial capital that the government is currently conceptualizing tourism development in the Lake Toba area. The concept of developing a tourist village in the Lake Toba area is very interesting, where the customs and culture of the people are combined with the natural beauty of Lake Toba to become a tourist attraction. The purpose of this study was to find out and analyze what was applied in the development of a tourist village in Meat village. The research method is a descriptive research method with a qualitative approach. The results of this study indicate that the development of tourist villages in Meat is still not optimal, where access, attractions, and amenities are not adequate. Forobstacles in the development of tourist villages in Meat village, budget constraints and lack of human resources in the field of tourism.